KELEMBAGAAN PUSAT KEGIATAN BELAJAR MASYARAKAT SEBAGAI AGEN PENGEMBANGAN MASYARAKAT - Entoh Tohani (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
The research was conducted to evaluate the performance of Community Learning Activities Center (CLAC) as an educational institution in empowering community. The research which is an evaluative study using the Stakes‘s evaluation model, took place at CLACs in Bantul, Yogyakarta Province. The findings show, firstly, each function of the CLACs has been put into practices. However, the implementation is not done effectively based on the criteria. It indicates that the performance is not organized professionally. Secondly, the CLACs have been able to produce meaningful learning outcomes such as creating positive behavior changes of targeted individuals or communities. However, the CLACs do not assign a greater impact on broader and multidimensional context of community empowerment.. Thirdly, there are threats that give negative influences on the implementation of the CLACs in terms of structural, interactional, and cultural aspects resulted from both internal and external environment of the CLAC institution. Therefore, bases on the findings, in the future the development of the CLACs should be planned and oriented to create the community toward more developed and comprehensive aspects of lives accompanied with the continuous development of strong commitment from stakeholders.